Features of the audit of construction enterprises - Humeha, V. V. (Ways to Improve Construction Efficiency, 2020)
The article defines the legal basis of the audit in Ukraine, theoretical approaches to the audit of construction companies, the issue of assessment by the auditors of the risks associated with the implementation of a project for housing construction. A construction audit is an independent assessment of both the financial and technical indicators of a construction investment project. This procedure involves checking the quality of construction work, determining the actual value of the object and the actual volume of construction. Building auditing is part of the management system and one of the most important components of the ISO 9001 quality system. As part of the funding expansion strategy, the audit of the organization is carried out as part of the audit in other areas of activity. Audit is conducted in two key areas: organization audit, project audit. It is determined that the construction audit is aimed at the study of common costs and pricing analysis, it is carried out at each stage of construction of the construction object. This process allows to identify the real volume of work, to determine the cost of finished products, to determine the quality of work performed at all stages of construction, to identify deviations from the project of the construction object. Audit of construction organizations is carried out in accordance with the general principles, but has its specificity, related to the legal form and features of the industry to which the contracting entity belongs, namely: regulatory regulation of the cost of construction works, features of determining the financial result of construction contracts , the presence of risks associated with the activities of construction companies. Audit in construction companies can be both proactive and mandatory. The main purpose of an audit in a construction organization – reliable, real and objective information about the implementation of construction contracts. Construction audits are carried out both on a separate site during the entire construction process and in a continuous manner by controlling all costs. In this article the main tasks of the audit of financial results are summarized and systematized, its peculiarities and main problems are defined, the recommendations on improvement of audit of financial results of construction organizations are given.